The poison diary of 1996 part - II - Abd Razak, Dzulkifli (1997)
IN THE MONTH OF JUNE TILL August last year, episodes of food poisoning gained prominence in the local scene. May be it's time we took a serious look at ourselves before matters get out of hand. The cholera outbreak could have turned into a nightmare. Other useful lessons that could be gathered between June and August are those related to control of tobacco in other parts of the world. Between June and August, many "unusual" poisoning cases occurred, underlying the fact that poisonings can indeed take place anywhere and everywhere, in many unsuspecting ways.